From soft and hard-nosed bankers: bank lending strategies and the survival of financially distressed firms - Daniel Höwer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Do private banks act as hard-nosed bankers when firms get financially distressed compared to public banks that have the mandate to support regional economy? For German firms in the period 2000-2005, I find that the probability of leaving the market after financial distress is higher for firms financed by private banks. The effects of different lending strategies are even larger for cooperative banks than for public banks.
Keywords: G21; G33; L14; 330; financially distressed firms; bank lending; public banks; cooperative banks; Kreditgeschäft; Krisenmanagement; Liquidation; Vergleich; Privatbank; Sparkasse; Kreditgenossenschaft; Deutschland